2023
DOI: 10.1155/2023/2766250
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota from Exercise Mice Counteracts High-Fat High-Cholesterol Diet-Induced Cognitive Impairment in C57BL/6 Mice

Abstract: Gut microbes may be the critical mediators for the cognitive enhancing effects of exercise. Via fecal microbiota transplantation (FMT), this study is aimed at determining the mechanism of how voluntary exercise improved learning and memory ability impairment post a high-fat, high-cholesterol (HFHC) diet. The learning and memory abilities assessed via the Morris water maze in the FMT recipient group of voluntary exercising mice were improved compared to sedentary group. 16S rRNA gene sequencing results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Klebsiella proliferate abnormally and colonize the gut, aggravating the inflammation in inflammatory bowel disease. 54 Interestingly, well-known SCFA-producing bacteria, including Lachnospiraceae _NK4A136_group, 55 Lactobacillus , 56 Roseburia , 57 and ASF356, 58 are inversely related to systemic inflammation. In addition, we found that treatment with A. muciniphila caused a significant elevation in the levels of SCFAs, such as acetic acid, propionic acid, isovaleric acid, butyric acid, isobutyric acid, and valeric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella proliferate abnormally and colonize the gut, aggravating the inflammation in inflammatory bowel disease. 54 Interestingly, well-known SCFA-producing bacteria, including Lachnospiraceae _NK4A136_group, 55 Lactobacillus , 56 Roseburia , 57 and ASF356, 58 are inversely related to systemic inflammation. In addition, we found that treatment with A. muciniphila caused a significant elevation in the levels of SCFAs, such as acetic acid, propionic acid, isovaleric acid, butyric acid, isobutyric acid, and valeric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific mechanisms by which SCFAs cause these effects are currently unknown, they still provide mechanistic insights into the treatment of AS by exercise. 16S rRNA sequencing as well as metabolomics analysis of fecal samples from mice after exercise intervention showed a significant increase in the total amount of SCFAs in the cecum ( Li et al, 2023 ). This finding reaffirms that exercise can affect the course of AS by influencing the gut microbiome.…”
Section: Resultsmentioning
confidence: 99%
“…Lower-intensity but sustained exercise can effectively reduce inflammation ( Paolucci et al, 2018 ), and this process may also be closely linked to the gut microbiome. SCFAs, for example, as described above, have regulatory roles in several signaling pathways in the human body and are primarily anti-inflammatory ( He et al, 2020 ) and that SCFAs expressed by the gut microbiome significantly increases after exercise ( Li et al, 2023 ). In addition, exercise is effective in relieving chronic systemic inflammation associated with aging ( Angulo et al, 2020 ), and given the age-related nature of AS, exercise management is uniquely valuable as a preventive and therapeutic measure for AS.…”
Section: Resultsmentioning
confidence: 99%
“…reported a rise in total SCFAs production in C57BL/6 mice after engaging in a voluntary wheel running program for 6 weeks (Estaki et al ., 2020 ). Furthermore, sedentary mice fed with a high-fat and high-cholesterol diet received FMT from C57BL/6J mice that underwent exercise had an increased total SCFAs concentration in their feces, as compared to those receiving FMT from sedentary animals (Li et al ., 2023 ). Among the SCFAs, butyrate seems to be notably affected by exertion.…”
Section: Exercise Influences Gut Microbiotamentioning
confidence: 99%